Chronic fluoride exposure-induced testicular toxicity is associated with inflammatory response in mice. (June 2016) - Wei, Ruifen; Luo, Guangying; Sun, Zilong; Wang, Shaolin; Wang, Jundong
Abstract: Previous studies have indicated that fluoride (F) can affect testicular toxicity in humans and rodents. However, the mechanism underlying F-induced testicular toxicity is not well understood. This study was conducted to evaluate the sperm quality, testicular histomorphology and inflammatory response in mice followed F exposure. Healthy male mice were randomly divided into four groups with sodium fluoride (NaF) at 0, 25, 50, 100 mg/L in the drinking water for 180 days. At the end of the exposure, significantly increased percentage of spermatozoa abnormality was found in mice exposed to 50 and 100 mg/L NaF. Disorganized spermatogenic cells, vacuoles in seminiferous tubules and loss and shedding of sperm cells were also observed in the NaF treated group. In addition, chronic F exposure increased testicular interleukin-17( IL-17 ), interleukin-17 receptor C ( IL-17RC ), tumor necrosis factor-α ( TNF-α ) and interleukin-6 ( IL-6 ) in transcriptional levels, as well as IL-17 and TNF-α levels in translational levels. Interestingly, we observed that F treated group elevated testicular inducible nitric oxide synthase ( iNOS ) mRNA level and nitric oxide (NO) concentration. Taken together, these results indicated that testicular inflammatory response could contribute to chronic F exposure induced testicular toxicity in mice. Highlights: Chronic fluoride exposure affected sperm quality. Chronic fluoride exposure injured testicular histomophology. Chronic fluoride exposure elevated expressions of testicular inflammatory mediators. Chronic fluoride exposure increased testicular NO concentration.